Antioxidant Properties and Cytoprotective Effect of Pistacia lentiscus L. Seed Oil against 7β-Hydroxycholesterol-Induced Toxicity in C2C12 Myoblasts: Reduction in Oxidative Stress, Mitochondrial and Peroxisomal Dysfunctions and Attenuation of Cell Death - Imen Ghzaiel (MDPI AG, 2021)
Aging is characterized by a progressive increase in oxidative stress, which favors lipid peroxidation and the formation of cholesterol oxide derivatives, including 7β-hydroxycholesterol (7β-OHC). This oxysterol, which is known to trigger oxidative stress, inflammation, and cell death, could contribute to the aging process and age-related diseases, such as sarcopenia. Identifying molecules or mixtures of molecules preventing the toxicity of 7β-OHC is therefore an important issue. This study consists of determining the chemical composition of Tunisian Pistacia lentiscus L. seed oil (PLSO) used in the Tunisian diet and evaluating its ability to counteract the cytotoxic effects induced by 7β-OHC in murine C2C12 myoblasts. The effects of 7β-OHC (50 µM; 24 h), associated or not with PLSO, were studied on cell viability, oxidative stress, and on mitochondrial and peroxisomal damages induction. α-Tocopherol (400 µM) was used as the positive control for cytoprotection. Our data show that PLSO is rich in bioactive compounds; it contains polyunsaturated fatty acids, and several nutrients with antioxidant properties: phytosterols, α-tocopherol, carotenoids, flavonoids, and phenolic compounds. When associated with PLSO (100 µg/mL), the 7β-OHC-induced cytotoxic effects were strongly attenuated. The cytoprotection was in the range of those observed with α-tocopherol. This cytoprotective effect was characterized by prevention of cell death and organelle dysfunction (restoration of cell adhesion, cell viability, and plasma membrane integrity; prevention of mitochondrial and peroxisomal damage) and attenuation of oxidative stress (reduction in reactive oxygen species overproduction in whole cells and at the mitochondrial level; decrease in lipid and protein oxidation products formation; and normalization of antioxidant enzyme activities: glutathione peroxidase (GPx) and superoxide dismutase (SOD)). These results provide evidence that PLSO has similar antioxidant properties than α-tocopherol used at high concentration and contains a mixture of molecules capable to attenuate 7β-OHC-induced cytotoxic effects in C2C12 myoblasts. These data reinforce the interest in edible oils associated with the Mediterranean diet, such as PLSO, in the prevention of age-related diseases, such as sarcopenia.